Between the Elite Power and Women Subordination: Formulation of "Dana Desa" in Java Village Context - M. Ali Sofyan; Rr. Wuri Arenggoasih (JSW (Jurnal Sosiologi Walisongo), 2022)
Dana desa (village funds) is one of the new policies to realize development based on the needs of rural communities. In its implementation there is a role that is often overlooked, it is women's role. This paper discusses the process of formulating dana desa policies in Pengalusan Village, with a focus on the role of women when formulating these policies. Applying the gender approach this study found that the planning process for the formulation of dana desa policies is carried out through the Musrenbangdes (village development planning meeting) which is carried out before the APBDes decision is agreed. But from the planning through evaluation processes there is no specific discussion related to the ideas, interests, and role of women in the development processes in the village. The elite as decision makers are men, and village development policies are more masculine, one of which is demonstrated through physical development. Women's ideas, roles and interests have not received enough attention in village development prosecces.